1995
DOI: 10.1089/end.1995.9.469
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriuria and Colonization of Double-Pigtail Ureteral Stents: Long-Term Experience with 237 Patients

Abstract: We prospectively studied 266 patients with indwelling double-pigtail ureteral stents to determine the incidence of stent colonization and associated bacteriuria. A urine culture was obtained just prior to stent insertion and was repeated at the time of its removal. The stent itself was also cultured. Of the 237 evaluable patients, 71 (29.9%) developed bacteriuria. Of the 237 stents, 161 (67.9%) became colonized with microorganisms. Pseudomonas aeruginosa was the most common pathogen isolated from the urine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
91
4
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 33 publications
14
91
4
4
Order By: Relevance
“…Since UTI and bacteriuria are more common in women than in men, this observation is comprehensible. Previous studies showed similar results [2][3][4]8]. The increase in MUSC in stents derived from patients older than 50 years might be associated with the age-related increase in bacteriuria.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Since UTI and bacteriuria are more common in women than in men, this observation is comprehensible. Previous studies showed similar results [2][3][4]8]. The increase in MUSC in stents derived from patients older than 50 years might be associated with the age-related increase in bacteriuria.…”
Section: Discussionsupporting
confidence: 63%
“…The role of CUC in predicting MUSC was discussed previously [2][3][4][5][6][7][8]. However, an exact differentiation between pathogens and contaminating organisms is missing in all studies, resulting in a higher rate of positive CUC when compared to our results.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In vitro and in vivo studies confirmed the difficulty in detecting biofilm formation by using conventional laboratory procedures [38,39]. Reid at al found that 90% of indwelling silicone double J stents were colonized by adherent bacteria, however the incidence of urinary infection detected clinically was only 27% [38].…”
Section: Ureteral Stentsmentioning
confidence: 93%
“…The difficulty in detecting biofilm formation by using conventional laboratory procedures was confirmed in a large study where 237 ureteral stents were tested. It was shown that 68% of stents were actually colonized but only 30% of patients were found to have bacteriuria [39]. Therefore, a negative urine culture does not rule out the possibility of stent colonization.…”
Section: Ureteral Stentsmentioning
confidence: 99%